Mechanical and Water Absorption Properties of Oil Palm Empty Fruit Bunch-High Density Polyethylene Composites - Arif, Muharnad Fatikul (2008)
High density polyethylene (HDPE) composites were fabricated using oil palm empty fruit bunch (EFB) as the reinforcing material. The effect of fiber content and fiber type, EFB particulate and short fiber, on the mechanical and water absorption properties of the composites were investigated. EFB short fiber composites experienced higher tensile and flexural properties compared to that of EFB particulate composites at all fiber contents. For EFB short fiber composites, tensile modulus, flexural strength and flexural modulus increased as the EFB content increased. Unlike that of the EFB short fiber composites, the tensile modulus and flexural strength of the EFB particulate composites increased as the EFB content increased up to 20%wt, but decreased at 30%wt fiber content, while the . flexural modulus constantly increased as the EFB content increased. The decrease in tensile strength was observed for both EFB particulate and short fiber composites as the EFB content increased. Study on water absorption of the composites revealed that EFB short fiber composites absorbed more water than that of EFB particulate composites. Both of EFB particulate and short fiber composites absorbed more water as the EFB content increased. The effects of chemical treatments on the mechanical and water absorption properties of the I O%wt EFB short fiber composites were also investigated. Alkali, acrylation and two types of silane treatments, y-methacryloxypropyltrimethoxysilane (MTS) and vinyltriethoxysilane (VTS) were employed. The optimum mechanical properties was achieved by treating the EFB with 10% alkali, 3% MTS, 3% VTS and 5% acrylic acid. Generally, the chemical treatments increased both of composite's tensile strength and tensile modulus. Among the four different types of treatments, the MTS treatment gave the highest increase in tensile strength of 9% compared to that of the untreated composites. To achieve the highest tensile modulus improvement, the acrylated treatment should be favored, with the increase of 10% compared to that of the untreated composites. The chemical treatments also increased composite's flexural strength and flexural modulus, except for the acrylation treatment, with an average increase of 6% and 18% compared to that of the untreated composites, respectively. The chemical treatments were found to decrease water absorption of the composites, with the highest water absorption resistance possessed by MTS treated composites, followed by VTS, acrylated and alkali treated composites. It could be inferred that the EFB particulate and short fiber composites have a variety of attractive properties to be used in thermoplastic composites of at least moderate strength. The mechanical properties and water uptake behavior were found to be improved upon chemical treatments such as alkali, acrylated and silane treatments. Keywords: oil palm empty fruit bunch, short fiber, particulate, composites, mechanical properties, water absorption, chemical treatment, alkali, acrylation, silane.